PELATIHAN PEMBUATAN SNACK BAR TEMPE DALAM UPAYA PENANGGULANGAN ANEMIA REMAJA PUTRI - Lestari, Utami Sasmita; Angmalisang, Elvin Clara; Wijaya, Nur Anindhita Kurniawaty (Jurnal Abdi Insani, 2024)
Anemia is the most common nutritional problem in the world. The increased need for iron in adolescents because they are in a period of growth makes adolescents very susceptible to anemia, especially in adolescent girls. Anemia can reduce fitness, productivity, learning ability, and cognitive abilities of adolescents. One effort that can be made to overcome anemia is providing tempe snack bar. Modifying tempe into tempe snack bars makes serving tempe more practical and preferred by adolescents. The purpose of this community service activity was to overcome the problem of anemia in adolescent girls by increasing the role of madrasah teachers through training in making tempe snack bars. The target of this service was madrasah teachers. The activity was carried out in the counseling stage, lectures and discussions about anemia and the benefits of tempe, especially in overcoming anemia in adolescent girls, followed by training in making tempe snack bars. The results of this community service activity hopely can be used as a solution to prevent and overcome anemia in adolescent girls. Providing motivation and awareness to adolescent girls to consume nutritious foods containing iron. This counseling activity is considered effective in changing the behavior of adolescent girls in preventing anemia. Keywords: anemia, tempe snack bar, adolescent, girls